A Remark on Wavelet Bases in Weighted 𝐿𝑝 Spaces - Agnieszka Wojciechowska (Journal of Function Spaces and Applications)
The paper deals with unconditional wavelet bases in weighted 𝐿𝑝 spaces. Inhomogeneous wavelets of Daubechies type are considered. Necessary and sufficient conditions for weights are found for which the wavelet system is an unconditional basis in weighted 𝐿𝑝 spaces in dependence on 𝑝.